2018
DOI: 10.1016/j.colegn.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Reducing occupational stress among registered nurses in very remote Australia: A participatory action research approach

Abstract: a b s t r a c tBackground: Nurses in very remote areas of Australia (RANs), work in complex and isolated settings for which they are often inadequately prepared, and stress levels are high. This paper, based on the 'Back from the edge' project, evaluates the development and implementation of an intervention to reduce and prevent the impact of occupational stress in the RAN workforce in the Northern territory. Methods: The methods involved a combined participatory action research/organisational development mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 18 publications
(18 reference statements)
2
34
0
Order By: Relevance
“…Given the high demand and under-resourced environment of the semi-rural hospital, organisational culture may potentially be the key to providing employees the opportunities to have a voice and the organisational support required of healthcare professionals. For example, in their study of occupational stress among nurses working in remote areas, Lenthall et al (2018) suggested that 'system capacity factors' such as the climate for worker psychological health, flexible/adaptable culture, consultation and preparation, and communication systems, could influence demands and resources. Indeed, remote work, social isolation and lack of support were key factors impacting occupational stress of nurses working in remote areas of Australia (Opie et al 2010).…”
Section: Organisational Culture As a Mechanism For Employee Voicementioning
confidence: 99%
“…Given the high demand and under-resourced environment of the semi-rural hospital, organisational culture may potentially be the key to providing employees the opportunities to have a voice and the organisational support required of healthcare professionals. For example, in their study of occupational stress among nurses working in remote areas, Lenthall et al (2018) suggested that 'system capacity factors' such as the climate for worker psychological health, flexible/adaptable culture, consultation and preparation, and communication systems, could influence demands and resources. Indeed, remote work, social isolation and lack of support were key factors impacting occupational stress of nurses working in remote areas of Australia (Opie et al 2010).…”
Section: Organisational Culture As a Mechanism For Employee Voicementioning
confidence: 99%
“…Significantly, RANs experience high levels of psychological distress and emotional exhaustion . Lenthall et al suggest that RANs have reported a lack of staff, being tired of orienting new staff, being concerned about the capability of in‐coming short‐term staff, being concerned about the continuity of care and feeling that remote communities can be demanding, detract from the RAN role. RANs have also reported being overwhelmed by the work and the after‐hours on‐call duty for emergency care .…”
Section: Introductionmentioning
confidence: 99%
“…Research, relating to the recruitment and staffing of RANs, has focused primarily on the views of RANs . This paper investigates the perspectives of RAN workforce issues among multiple stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…There appears to be a relationship between various job demands/resources and nurses’ overall well‐being in their workplaces. With few exceptions (Lenthall et al, ), the majority of these studies involving nurses have been hospital‐based and use a limited set of researcher‐defined indicators of both job demands and resources, with less reliance on psychometrically sound and integrated measures. This article describes the development, pilot testing and psychometric evaluation of two new scales measuring the global (i.e., applicable to a broad range of nursing designations and practice settings) Job Resources in Nursing (JRIN) and Job Demands in Nursing (JDIN) as part of a nationwide cross‐sectional survey involving nurses in a wide range of workplaces in rural and remote communities.…”
Section: Introductionmentioning
confidence: 99%